2015
DOI: 10.1007/s11947-015-1478-z
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest Handling and Storage of Fresh Cassava Root and Products: a Review

Abstract: The increase in global demand for healthy food products and initiatives to ensure food security in developing countries has focused on the cultivation of drought-resistant and biofortified cassava varieties. Cassava is a staple root crop grown in subtropical and tropical climates. Cassava flour is gluten free, which can be used as composite flour in essential foods such as bread. Thus, the role of postharvest handling of freshly harvested cassava root is essential, owing to the rapid physiological deterioratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 101 publications
0
79
0
1
Order By: Relevance
“…Minimal processing of fruits and vegetables physically changes the products without modifying their sensory characteristics. It is appropriate for cassava because of the high perishability of the roots, low postharvest value‐added marketing, and lengthy preparation (Barrett, Beaulieu, & Shewfelt, ; Uchechukwu‐Agua, Caleb, & Opara, ). Nevertheless, handling during the stages of minimal processing promotes damage to the cassava roots, leading to an increased respiratory rate, and the accumulation of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
“…Minimal processing of fruits and vegetables physically changes the products without modifying their sensory characteristics. It is appropriate for cassava because of the high perishability of the roots, low postharvest value‐added marketing, and lengthy preparation (Barrett, Beaulieu, & Shewfelt, ; Uchechukwu‐Agua, Caleb, & Opara, ). Nevertheless, handling during the stages of minimal processing promotes damage to the cassava roots, leading to an increased respiratory rate, and the accumulation of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its ease of digestibility and its cholesterol‐lowering, hypoglycemic and antidiabetic effects, cassava starch has been used in various food products, including garri, agbelima and bread . Cassava starch has similar digestibility to taro and rice, but it is unaffected by variety, drying process, grinding degree or plant age .…”
Section: Cassava Starchmentioning
confidence: 99%
“…For example, quantitative proteomics data demonstrated that reducing ethene biosynthesis and increasing enzymes involved in suberization and lignification could further delay PPD onset in cassava roots . Therefore adopting novel postharvest handling, processing, packaging and storage techniques might further increase the postharvest shelf‐life and economic value of cassava root …”
Section: Problems and Challengesmentioning
confidence: 99%
See 2 more Smart Citations